Organization of rear protection of the 1st Belorussian Front in the Berlin operation - Wojcieszak, Andrzej (City and War, 2021)
The course of each of the wars is characterized by various types of solutions in the field of logistic security, usually implemented in very extreme conditions. These solutions are often of fundamental importance for the course of combat operations. The Berlin Operation, the Battle of Berlin (in Soviet and Russian historiography as the Berlin Strategic Offensive Operation) – an offensive operation carried out between April 16 and May 2, 1945 with the forces of three Red Army fronts. Its goal was to conquer Berlin. The logistics of the Soviet troops during World War II reached a climax of development, hitherto unknown, taking into account the needs of troops participating in the fighting during large offensive strategic operations. The content of the article presents selected issues concerning the rear protection of the troops of the 1st Belorussian Front. The conditions that determined its planning and organization were presented, and the final results of the work performed were indicated. The tasks and the model of the organization of the rear of the front as well as the arrangement of the essential elements and rear devices were discussed. The aim of the article is to popularize issues related to the rear support of hostilities. According to the author, this aspect is often overlooked, usually treated very briefly or even underestimated, not to say even neglected by military historians, an aspect accompanying every armed conflict. Looking at the course of military operations through the prism of logistics, we see a completely different face of the war. You can then fully understand the words of the Swiss general A.-H. Jomini’s: “Logistics is all or almost all military activities, except for combat”. The history of the army and wars is closely related to the history of logistics. There have always been logistical problems since the beginning of warfare. They were the basic condition for the success of all kinds of activities because their purpose was to satisfy the material and other needs of soldiers and the combat equipment used by them. The way logistics function on the battlefield contributes to the development of military thought and the art of war to a varying degree. The history of wars provides us with many examples that sometimes small innovations or the implementation of unconventional solutions can change the course of history and turn the tide of victory.